Profiles of Deceased Patients with Coronavirus Disease 2019 (COVID-19) and Multidrug-Resistant Bacterial Coinfections at an Indonesian Tertiary Hospital - Joedhistira Bayu Firmansyah; Musofa Rusli; Juniastuti; Ratna Septyawati (Current Internal Medicine Research and Practice Surabaya Journal)
Introduction: Antibiotic use in coronavirus disease 2019 (COVID-19) patients reached 70% during the pandemic, potentially inducing the invasion of multidrug-resistant organisms (MDROs). This study analyzed patients who died from COVID-19 with MDRO coinfections at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia.